Performance analysis of inductive power transfer using JMAG-designer - Mahadi, Ismail Ahmat; Yahaya, Jabbar Al-Fattah (Institute of Advanced Engineering and Science, 2023)
Due to its advantage of sending electrical power from the transmitter source to the receiver load with no physical contact, wireless power transfer (WPT) has rapidly gained popularity in recent years. They can be used in a variety of applications, including induction cooking, mobile phone charging, radio frequency identification (RFID), and electric vehicles (EVs). Using JMAG-designer, a simulation of series-parallel inductive power transmission has been investigated in this research. This study aims to determine how the output power and efficiency change depending on how many coils turn in the transmitter and receiver. The number of coils turn in the transmitter is fixed which is 20 turns, the number of coils turn in the receiver is variable and ranges between 15 and 30, and the air gap or distance between the coupling coils is set at 10 cm. The selected frequency to be used in this simulation is between 10 and 50 kHz. According to the absorption result, the output power and efficiency rise when the receiver has more coil turns than the transmitter, and the output power and current rise along with an increase in resonance frequency.